Staging the lyric modern and contemporary experiments with verse drama - Berry, Sarah (Methuen Drama, 2025)
"Verse drama is not a dead form, but very much alive on the contemporary stage. Drawing on plays from throughout the English-speaking world, including the United States, United Kingdom, Ireland and the Caribbean, Staging the Lyric compares contemporary plays with modernist ones that experiment with the tension between the lyric and the dramatic. Chapters trace a genealogy from contemporary plays by Joanna Laurens, Joyelle McSweeney, and David Grieg back to W.B. Yeats, T.S. Eliot, and W.H. Auden to reveal that the tensions that animate verse drama have stayed the same, even as the strategies for staging them have evolved."
Keywords: Verse drama, English / History and criticism; Verse drama, American / History and criticism; Theater / Great Britain / History; Theater / United States / History